The Role of Long Non-Coding RNAs in Thyroid Cancer - Peng, Xuejiao; Zhang, Kun; Ma, Li; Xu, Junfeng; Chang, Weiqin (Frontiers in Oncology, 2020)
Thyroid cancer, the most common endocrine malignancy, has become one of the most increasingly common malignant solid tumors in recent years. Moreover, some cases have a poor prognosis, and the survival period is only 3–5 months. Recent studies have discovered important roles for long non-coding RNAs during the complex process of carcinogenesis in thyroid cancer. lncRNAs are a group of functional RNA molecules more than 200 nucleotides in length that lack the ability to encode protein but participate in all aspects of gene regulation. Functionally, many lncRNA have essential roles to play in epigenetic regulatory at transcriptional and post-transcriptional levels via various molecular mechanisms. In this review, we mainly focus on lncRNAs that are dysregulated in thyroid cancer and summarize recently reported associations between lncRNAs and thyroid cancer in an effort to demonstrate the significant value of lncRNAs in the diagnosis and treatment .